Classical Swine Fever Virus Infection in India: Seroprevalence Study from North-eastern States of India - AHUJA, ANUJ; MUKHARJEE, PRIYANKA; BHATTACHARJEE, UTTARAN; CHAKRABORTY, AMIT KUMAR; KARAM, AMARJIT; GHATAK, SANDEEP; PURO, KEKUNGU; DAS, SAMIR; SHAKUNTALA, INGUDAM; SRIVASTAVA, NIDHI; SEN, ARNAB (Indian Journal of Hill Farming, 2015)
A pilot study was undertaken regarding the prevalence of classical swine fever virus (CSFV) antibodies sera samples of domestic pigs from two north-eastern states, Meghalaya and Manipur. The samples were received and collected between 2011 and September 2013. A total of 516 serum samples from 2 states of north-east region were tested using commercial enzyme-linked immunosorbent assay (ELISA) kits. The mean prevalence of CSFV antibodies in suspected sera was 45.54% (235/516). State wise prevalence of CSFV antibodies was 52.27% and 38.49% from Meghalaya and Manipur respectively. The high prevalence of CSFV antibodies suggests that the disease is endemic in the country. This baseline data will be of use in the formulation of control and eradication programmes.